Bagaimana Perusahaan Melakukan Penghindaran Pajak di Indonesia? - Farrel Ewaldo Rafa; Juli Ratnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Tax Amnesty, profitability, leverage, and firm size on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. Tax avoidance practices are a serious concern because they can reduce potential state revenue. This research uses agency theory as a theoretical basis to explain the conflict of interest between management and shareholders regarding profit reporting and tax payments. The results of this study are expected to contribute to academic literature, practitioners, and regulators in an effort to improve the effectiveness of the taxation system in Indonesia.